2008
DOI: 10.1021/ma800562s
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Sensitive Poly(caprolactone-co-trimethylene carbonate)−Poly(ethylene glycol)−Poly(caprolactone-co-trimethylene carbonate) as in Situ Gel-Forming Biomaterial

Abstract: We are reporting a new thermogelling poly(caprolactone-co-trimethylene carbonate)-poly(ethylene glycol)-poly(caprolactone-co-trimethylene carbonate) (PCTC-PEG-PCTC) triblock copolymer. By incorporating the comonomer (trimethylene carbonate) up to 25-40 wt % in the polycaprolactone block, the resulting PCTC-PEG-PCTC triblock copolymer achieved sol stability while keeping the thermogelling property in a physiologically important temperature range of 10-50 °C. The precipitation of the polymer in water at 20 °C wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 36 publications
1
50
0
2
Order By: Relevance
“…The crystallization of the PCL block is partially reduced by copolymerizing caprolactone with lactide or trimethylene carbonate. 14,15 Pluronics Are Still Attractive Thermogels Aside from the research on thermogelling polyesters of PLGA and PCL, multiblock copolymers of Pluronics have been designed to solve the short gel duration problem of Pluronics. The mutiblock Pluronics are connected by terephthalate, 2,5-dicarboxy terephthalate, and disulfide ( Figure 5).…”
Section: How To Shorten the Dissolution Timementioning
confidence: 99%
“…The crystallization of the PCL block is partially reduced by copolymerizing caprolactone with lactide or trimethylene carbonate. 14,15 Pluronics Are Still Attractive Thermogels Aside from the research on thermogelling polyesters of PLGA and PCL, multiblock copolymers of Pluronics have been designed to solve the short gel duration problem of Pluronics. The mutiblock Pluronics are connected by terephthalate, 2,5-dicarboxy terephthalate, and disulfide ( Figure 5).…”
Section: How To Shorten the Dissolution Timementioning
confidence: 99%
“…Thus, gel duration of PEG–PCL–PEG thermogel could be controlled by designing a PEG–PCL–PEG with an oxalate bond at the middle of the triblock copolymer. Previously, gel duration of PCL was controlled by copolymerization of caprolactone and lactide or glycolide . However, the copolymerization led to loss of crystallinity of PCL, which provided powder morphology of the polymer .…”
Section: Resultsmentioning
confidence: 99%
“…Calcium ammoniate, HCl/Et 2 A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 The morphologies of the self-assemblies in PEG-PCL diblock copolymers aqueous solution were highly dependent on the length of the building blocks. For example, Xu and his coworkers reported that the micellar morphology of PEG-PCL block copolymers in water can be regulated by crystallization temperatures.…”
Section: Diblock Copolymers and Their Self-assembliesmentioning
confidence: 99%
“…Such structure and functionality tailoring of PCL produces desired polymers with superior properties for a wide variety of applications including targeted drug delivery, sustained gene delivery, injectables and three dimensional (3D) cell encapsulation in tissue engineering. [1][2][3][4][5][6][7][8][9][10] In this review, the most intensively studied PCL based amphiphilic block copolymers are discussed in terms of their different architectures and various self-…”
Section: Introductionmentioning
confidence: 99%